2009
DOI: 10.1039/b819454h
|View full text |Cite
|
Sign up to set email alerts
|

A concise total synthesis of (±)-anthecularin

Abstract: A total synthesis of the novel sesquiterpene anthecularin 1, isolated from Greek Anthemis auriculata, based on an intramolecular [5+2] (1,3-dipolar) cycloaddition involving the oxidopyrylium ion 12 derived from the furanmethanol 9, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Table 1 lists the binding constants of some representative dyes with cucurbiturils and cyclodextrins in aqueous solution. [21][22][23][24] As seen in Table 1, CB [7] forms moderately stable complexes with positively charged guests in buffer solution, showing a K S order of 2 > 1 > 3 in pH 6.0 buffer solution. A reasonable explanation for the highest binding ability of CB [7] towards 2 is that CB [7] can effectively bind the positive-charge portion of 1 or 3 mainly through ion-dipole interactions, while for 2, the hydrogen bond interactions between the middle NH group in 2 and C=O group in CB [7] possibly also play a crucial role in the host-guest complexation besides the ion-dipole interactions.…”
Section: Molecular Selective Binding Of Cucurbiturils Vs Cyclodextrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 lists the binding constants of some representative dyes with cucurbiturils and cyclodextrins in aqueous solution. [21][22][23][24] As seen in Table 1, CB [7] forms moderately stable complexes with positively charged guests in buffer solution, showing a K S order of 2 > 1 > 3 in pH 6.0 buffer solution. A reasonable explanation for the highest binding ability of CB [7] towards 2 is that CB [7] can effectively bind the positive-charge portion of 1 or 3 mainly through ion-dipole interactions, while for 2, the hydrogen bond interactions between the middle NH group in 2 and C=O group in CB [7] possibly also play a crucial role in the host-guest complexation besides the ion-dipole interactions.…”
Section: Molecular Selective Binding Of Cucurbiturils Vs Cyclodextrinsmentioning
confidence: 99%
“…However, because of the intense charge repulsion between the carboxylate group of guest 8 À and the carbonyl oxygens on the CB [7] portals, the negatively charged guest 8 À is not bound at all by CB [7], although all of these ferrocene-containing guests can form stable inclusion complexes with b-CD regardless of their charge. [22][23][24] From the results described above, one can conclude that CB [7] is a better host for cationic guests than b-CD, especially in pure water. It should be noted that the addi-tion of salt greatly affects the binding abilities of cucurbiturils in aqueous solution.…”
Section: Molecular Selective Binding Of Cucurbiturils Vs Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have an ongoing interest in the use of simple α‐carbonyl compounds to synthesize stereogenic C−F centers . Very recently, we showed that weakly acidic α‐fluoro carboxylate esters are competent fluorocarbon reagents that can be converted to α‐fluoro‐β‐amino acid derivatives through a highly diastereoselective Mannich reaction . Herein, we disclose an efficient Mannich reaction between 3‐fluorooxindoles and Ellman's imines to provide access to a wide variety of β‐amino amides containing α‐fluorinated stereogenic carbon centers (Scheme ).…”
Section: Figurementioning
confidence: 99%
“…In 2009, Pattenden et al reported a concise total synthesis of the sesquiterpene anthecularin, a natural product exhibiting anti-malarial activity. [65] This synthesis was based on the intramolecular [5 + 2] cycloaddition of the acetoxypyranone-substituted butenolide 93. Indeed, when a solution of 93 in toluene containing DBU was heated under reflux for 1 h, the cycloaddition involving the corresponding oxidopyrylium species took place, leading to the tetracyclic product 92, albeit in low yield (15-20%), as illustrated in Scheme 40.…”
Section: Intramolecular [5 + 2] Cycloadditions Of Oxidopyrylium Ionsmentioning
confidence: 99%